SIDE EFFECTS OF ANTIDEPRESSANTS ON ORAL HEALTH ACCORDING TO QUESTIONNAIRES OF PATIENTS AND HEALTHCARE PROFESSIONALS - Khaitovych, M.V.; Mazur, I.P.; Voitova, Ya.V.; Yunakova, N.M.; Turchak, D.V.; Temirova, O.A.; Polyakova, D.S. (World of Medicine and Biology, 2023)
An anonymous survey was conducted of 31 visitors to pharmacies with prescriptions for antidepressants, 30 doctors who prescribe antidepressants, 51 pharmacy employees and 40 dentists. Less than half of doctors who prescribe antidepressants, pharmacists and only 12.9 % of patients were informed about the risk of adverse reactions from the oral cavity when using antidepressants. Complaints about the presence of caries or dryness/ulcers on the oral mucosa were noted in the questionnaires of 26 (83.9 %) patients. According to the data of 82.5 % of dentists, patients came to them with complaints of dry mouth due to the use of antidepressants. Therefore, among patients who use antidepressants, a high prevalence of caries and its complications, as well as the development of periodontal diseases against the background of dry mouth, was found, which may be partly related to the increase in the use of tricyclic antidepressants and the low awareness of patients and health care professionals about the peculiarities undesirable effects of antidepressants on the oral cavity condition.